Development of Irrigation and Drainage System in a Changing Environment: A Way Forward - Daniele De Wrachien (Research Highlights in Agricultural Sciences Vol. 5, 2022)
The world population is expected to grow from almost 6 billion today to at least 8 billion by 2025.Globally, prospects of increasing the gross cultivated area are limited by the decrease of suitable sites for land reclamation or large-scale irrigation and drainage projects. These issues have to be analysed in light of the expected impacts of climate change and environmental sustainability. The paper highlights the impacts of these issues on the need to increase food production and for sustainable irrigation and drainage development and management.